PENENTUAN TARIF JASA RAWAT INAP MENGGUNAKAN METODE ACTIVITY BASED COSTING - Novi Fadhila; Chintya Maramis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara)
The calculation method in determining the rate of inpatient hospital services is very important. If the inpatient rate calculation method used is not suitable to be applied, there will be cost distortion. Cost distortion occurs due to inaccuracies in costing, so that it will result in errors in determining costs and making decisions. The purpose of this research is to find out how to determine inpatient service rates using activity based costing and to see the magnitude of the comparison of inpatient service rates with traditional systems and activity based costing at Muhammadiyah Hospital of North Sumatra. This type of research in this research is comparative descriptive. Data collection techniques were carried out by means of interviews and documentation. The data analysis technique used is descriptive quantitative by looking at the hospitalization rates by the Muhammadiyah Hospital of North Sumatra then calculating the inpatient rates using activity based costing, after getting the results, we can see the difference. The results of the study of inpatient service rates at Muhammadiyah Hospital of North Sumatra with Activity Based Costing gave cheaper results in VIP and Class I. Classes II and III gave more expensive results. This difference occurs because in Activity Based Costing the overhead costs of each product are charged to many cost drivers. So that in Activity Based Costing has been able to allocate activity costs to each room appropriately based on the consumption of each activity.